Effectiveness of OER Use in First-Year Higher Education Students’ Mathematical Course Performance: A Case Study - Venegas Muggli, Juan Ignacio; Westermann, Werner (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2019)
This article examines the effect of two Open Educational Resources (OER) - Khan Academy Collection and a teacher-authored open textbook - on mathematical course performance and attendance amongst first-year higher education Chilean students. It also aims to find out about teachers’ and students’ views on the use of OER in order to understand how these resources are used and valued. To this end, quantitative and qualitative methods were employed. Findings indicate that students in face-to-face classes who used Khan Academy resources obtained better examination grades than students who used the open textbook or relied on traditional proprietary textbooks. Moreover, it was also found that students who used both types of OER had significantly lower attendance levels than students who relied on traditional proprietary textbooks. Finally, it was observed that teachers and students had very positive opinions on the use of both the Khan Academy Collection and open textbook resources.